Global distribution of 7Be, 210Pb and, 210Po in the surface air (with Appendix A-E) - Persson, Bertil R (Bertil RR Persson, Medical Radiation Physics, 22185 Lund, Sweden, 2016)
In the effort of modelling the global distribution 7Be, 210Pb and 210Po in surface air, the results from exploration of radioactivity exploration from the Arctic to the Antarctic during 1980 to 1996 are compiled with the results reported by other authors. Partial least square regression modelling PLS-regression, predict missing 7Be, 210Pb and 210Po values of air concentration or annual deposition. All available data of air concentration and deposition, of these radionuclides are then correlated with geophysical parameters. The results indicate that the global latitudinal distribution of 7Be air concentration was rather flat, with an overall global average of 4.2 (SE 0.4) mBq.m-3, although with a slight dip at the equator and decrease towards high latitudes. The corresponding latitudinal distribution was also flat, and decreased slightly at high and low altitudes, with overall global average of 7Be annual deposition was 1500 (SE 100) Bq.m-3.a-1. The 7Be deposition rate estimated from reported annual mean air concentration and annual deposition is 13.4 +/- 1.7 (SE) mm.s-1. By using PLS-r modelling of either air concentrations or annual depositions, the average deposition rate of 7Be was estimated to 12.3 +/- 1.6 (SD) mm.s-1. The 7Be deposition-rate don´t vary significantly with longitude, latitude or geometrical average year of sampling date. Linear regression with height, however, is negative with a coefficient of - 0.02. At sea level, the 7Be deposition-rate was estimated to 13 mm.s-1, while at a height of 800 m it was predicted to be 7 mm.s-1. The 16 values of 7Be deposition rate, reported in the literature, are widely scattered (SD = 18) with an average of about 18 mm.s-1. The latitudinal distribution of the activity concentration of 210Pb in air showed a maximum of about 600 +/- 200 micoBq.m-3 around 45 oN with a steady decrease towards higher and lower latitudes. Minimum values of 400 micoBq.m-3 and 80 micoBq.m-3 were estimated at 90 oN and at 90 oS respectively. The latitudinal distribution of all 210Pb air ...